Impact of GnRH antagonist duration on IVF outcome - Ozkan, Z. S.; Simsek, M.; Kumbak, B.; Atilgan, R.; Sapmaz, E. (Oxford Univ Press, 2012)
[Abstract Not Available]
28th Annual Meeting of the European-Society-of-Human-Reproduction-and-Embryology (ESHRE) -- JUL 01-04, 2012 -- Istanbul, TURKEY